1998
DOI: 10.1136/ard.57.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Expression of alpha  and beta  subunits of the integrin superfamily in articular cartilage from macroscopically normal and osteoarthritic human femoral heads

Abstract: Objective-The objective of this study was to detail the topographical and zonal distribution of and subunits of the integrin superfamily in normal and osteoarthritic cartilage. Methods-Immunohistochemistry utilising antibodies towardsand subunits was performed on cryostat sections of human articular cartilage from macroscopically normal (n = 6) and osteoarthritic (n = 6) femoral heads. Samples of articular cartilage were obtained from 12 topographically distinct sites from each femoral head. Each section was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 40 publications
6
65
0
3
Order By: Relevance
“…Nonetheless, ␣v␤5 integrin could be another important integrin in chondrocytes. The results of previous studies, along with the findings of the present study, consistently indicate that ␣v␤5 integrin is abundantly expressed on articular chondrocytes (19,20) and that ␣v␤5 integrin mediates chondrocyte attachment to various matrices (45,46). Therefore, it would not be surprising to find that ␣v␤5 integrin is involved in the metabolic and morphologic changes that occur in monolayer-cultured chondrocytes after plating.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, ␣v␤5 integrin could be another important integrin in chondrocytes. The results of previous studies, along with the findings of the present study, consistently indicate that ␣v␤5 integrin is abundantly expressed on articular chondrocytes (19,20) and that ␣v␤5 integrin mediates chondrocyte attachment to various matrices (45,46). Therefore, it would not be surprising to find that ␣v␤5 integrin is involved in the metabolic and morphologic changes that occur in monolayer-cultured chondrocytes after plating.…”
Section: Discussionsupporting
confidence: 88%
“…(Data are available online at http://www.hosp.go.jp/ϳsagami/rinken/crc/index.html.) Although the microarray used for the analysis did not contain the probe for ␣1 integrin, previous studies have shown that it is a dominant integrin in human articular chondrocytes (19,20,28). Thus, we focused our investigation on the significance of these 11 integrins in the dedifferentiation of monolayer-cultured articular chondrocytes.…”
Section: Determination Of Dominant Integrins In Human Articular Chondmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study cannot exclude the possibility that HA-CD44 interaction could inhibit the action of HBFN-f through binding to other receptor(s) on chondrocytes. Integrin α4β1 is expressed on chondrocytes in OA cartilage (17,27) but not normal (27). As shown in our previous studies in RA synovial fibroblasts (42), HBFN-f may act through this integrin in OA and RA chondrocytes.…”
Section: Correlation Of Cd44 Levels With Hbfn-f-stimulated No Productmentioning
confidence: 78%
“…In adult joints, increased immunostaining of ␤1 integrin was reported in osteoarthritic monkey cartilage compared with normal cartilage (14) and in human OA samples at minimally damaged locations compared with areas with more severe lesions (15). In another study, the neoexpression of ␣2, ␣4, and ␤2 integrins was observed in osteoarthritic human femoral head cartilage (16). In vitro experiments have suggested that signaling through the fibronectin (FN) receptor ␣5␤1 integrin is pivotal to prevent cell death of normal and osteoarthritic human articular chondrocytes (17).…”
Section: -Col2a1crementioning
confidence: 82%